Mutagen Killing and Photoreactivation in the Anaerobic Fungus Neocallimastix frontalis EB188 - R. E. Calza; E. M. Barichievich (Fungal Genetics Reports, 1996)
Research was performed to determine if the anaerobic fungus, Neocallimastix frontalis EB 188, a common cellulolytic fungus of ruminants, is capable of photoreactivation and is susceptible to chemical and irradiational mutagenesis. Germination of zoospores and production of colony cellulase was measured after ultraviolet light (UVL), nitrosoguanidine or ethyl methyl sulfonate treatments. This fungus was susceptible to mutagen treatment and capable of photoreactivation after UVL exposure. Such procedures may be useful in the isolation of enhanced cellulase-producing strains.